Comparison of Low-temperature District Heating Concepts in a Long-Term Energy System Perspective - Lund, Rasmus; Østergaard, Dorte Skaarup; Yang, Xiaochen; Mathiesen, Brian Vad (International Journal of Sustainable Energy Planning and Management, 2017)
District heating systems are important components in an energy efficient heat supply. With increasing amounts of renewable energy, the foundation for district heating is changing and the approach to its planning will have to change. Reduced temperatures of district heating are proposed as a solution to adapt it to future renewable energy systems. This study compares three alternative concepts for district heating temperature level: Low temperature (55/25 oC), Ultra-low temperature with electric boosting (45/25 oC), and Ultra-low temperature with heat pump boosting (35/20 oC) taking into account the grid losses, production efficiencies and building requirements. The scenarios are modelled and analysed in the analysis tool EnergyPLAN and compared on primary energy supply and socioeconomic costs. The results show that the low temperature solution (55/25 oC) has the lowest costs, reducing the total costs by about 100 M€/year in 2050.